Italijansko-slovenski jezikovni stik med ideologijo in pragmatiko - Grgič, Matejka (Jezik in slovstvo, 2017)
The article focuses on the current situation of the Slovenian language in Italy, in particular among the community of speakers who identify themselves with the Slovenian national minority. It analyses certain sociological, anthropological and psychological aspects emerging from the speakers' discourses about their perceptions and representations of the language. The paper highlights the Slovenian-Italian language contact area, especially those contexts where the Slovenian language is not the primary language of the speakers and the wider community. Reflection on both the language phenomena and the discourses provides a general overview of the current situation. Moreover, the analysis could be a good theoretical basis for future language planning programmes and policies, and for related implementation strategies. It also provides a good starting point for a critical analysis of models and options that have so far been taken for granted.
Keywords: Slovene; slovenščina; sociolinguistics; sociolingvistika; jezikovna politika; jeziki v stiku; jezkovna ideologija; manjšine; Italija; Italy